ANALISIS PENDAPATAN USAHA PETERNAKAN SKALA MENENGAH PROGRAM UMKM PADA RUMAH PEMOTONGAN AYAM KAMPUNG(STUDI KASUS RPA LA’TANSA DI KECAMATAN PALU SELATAN KELURAHAN BIROBULI UTARA) - Riandhana, Taufiq Eka; Indriani, Indriani; Ashad, Ashad; Rahayu, Ritha; Maksum, Haerani (SINERGI : Jurnal Riset Ilmiah, 2024)
Central Sulawesi Province has an area of ​​61,841.29 km^2 consisting of 13 Regencies/Cities with a population of 2,921,715 people or 719,031 households and a population of 77,004 free-range chickens spread across several areas of Palu City (Central Statistics Agency, 2016). Palu City as an autonomous region has various resources that can be developed to achieve the main goal of economic development, so that it can increase the number and types of employment opportunities for regional communities so that community welfare is more equitable. In an effort to achieve this goal, the government must be able to develop potential economic sectors, one of which is free-range chicken farming so that it develops as a leading sector. With the hope that this sector will be able to contribute to the community's economy, especially medium-sized farms with MSME capital. Extensive-traditional or free range chicken rearing system. Even though there are breeders who carry out intensive cultivation, they are still very limited in terms of capital and marketing. This is what makes the total production of the free-range chicken population in the city of Palu lower when compared to other cities, so it is necessary to conduct a study on income analysis of the medium-scale free-range chicken business for the UMKM program in the City of Palu. The aim of this research is to find out how much income middle-scale chicken traders earn from the MSME program at RPA LA Tansa, South Palu District, North Bureaubuli Village and to find out the feasibility of selling free-range chickens at RPA Latansa. This research will be carried out at RPA Latansa from February to April 2024 . This research method uses a survey method. The research design uses a type of quantitative descriptive research, namely a research procedure that uses descriptive data in the form of written or spoken words (interviews) with respondents, then the research data obtained is simplified in table form by displaying the number and average, then analyzed again sequentially. descriptive. The data analysis used is Revenue Analysis, Cost Analysis, Income Analysis and R/C Ration business feasibility analysis. Based on an analysis of income calculations, the Latan'sa chicken slaughterhouse (RPA) business income for one month is IDR. 38,722,708 which shows that the Latan'sa chicken slaughterhouse (RPA) business is making a profit